The organizational structure of Electric Machine Industry in the Ukrainian in 1922 - 1941 years - Annenkov, I. A. (History of science and technology, 2015)
This research represents block diagrams of Ukrainian electrical engineering management system from the date of Ukraine entered the USSR until 1941. Carried out analysis for their compliance to current and prospective challenges set by the industry. The research defines the levels of optimal management principles in organizational component of scientific and technical potential of national electrical engineering in the conditions of the country’s industrialization.